1989
DOI: 10.1258/002367789780863628
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of mutant mice (ICGN) with spontaneous renal lesions: a new model for human nephrotic syndrome

Abstract: Spontaneous nephrotic mice (ICGN mice), a new mutant strain of mouse from outbred ICR, were clinically, macroscopically, histologically and immunohistochemically studied to establish their value as a model for human nephrotic syndrome. Most of the affected mice developed proteinuria, hypoproteinaemia and hypercholesterolaemia, and some of them developed systemic oedema. A high concentration of blood urea nitrogen (BUN) and a low haematocrit value were also observed. The kidneys of severe cases showed a decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
77
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(79 citation statements)
references
References 0 publications
2
77
0
Order By: Relevance
“…When the degradation of ECM is required, the appropriate TIMP is removed from the MMP via digestion by a proteolytic enzyme (ex. Plasmin, MT-MMP and so on), and pro-MMP is activated and the against ECM.ICR-derived glomerulonephritis (ICGN) mice develop severe proteinuria at an early age which progresses to nephrosis [7,8]. This strain suffers from hypoalbuminemia, hypercholesterolemia, and anemia.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…When the degradation of ECM is required, the appropriate TIMP is removed from the MMP via digestion by a proteolytic enzyme (ex. Plasmin, MT-MMP and so on), and pro-MMP is activated and the against ECM.ICR-derived glomerulonephritis (ICGN) mice develop severe proteinuria at an early age which progresses to nephrosis [7,8]. This strain suffers from hypoalbuminemia, hypercholesterolemia, and anemia.…”
mentioning
confidence: 99%
“…ICR-derived glomerulonephritis (ICGN) mice develop severe proteinuria at an early age which progresses to nephrosis [7,8]. This strain suffers from hypoalbuminemia, hypercholesterolemia, and anemia.…”
mentioning
confidence: 99%
“…It is affected by heavy proteinuria, hypoalbuminemia, hypercholesterolemia, systemic edema and anemia. Histological studies show a thickened glomerular basement membrane (GBM) and effacement of podocyte foot processes at an early age [9][10][11][12][13][14]. We previously found that components of the extracellular matrix (ECM) accumulate in the glomeruli and tubulointerstitium of ICGN kidneys [2,3,19], and that the accumulation was due to hyper-production and less degradation of the ECM components [20,21,23].…”
mentioning
confidence: 99%
“…Compared with these experimental animals, the ICR-derived glomerulonephritis (ICGN) mouse established in the National Institute of Infectious Diseases (NIID; Tokyo, Japan) is a superior nephrotic model exhibiting chronic renal failure without any special management. The ICGN mouse is a novel inbred mouse strain with a hereditary nephrotic syndrome of unknown etiology, and is considered to be a good model of human idiopathic nephrotic syndrome [20][21][22]. Homozygous ICGN mice exhibit proteinuria at a young age, later develop hypoproteinemia, hyperlipidemia, severe anemia and systemic edema, and eventually die as a result of CRD [20,21].…”
mentioning
confidence: 99%
“…The ICGN mouse is a novel inbred mouse strain with a hereditary nephrotic syndrome of unknown etiology, and is considered to be a good model of human idiopathic nephrotic syndrome [20][21][22]. Homozygous ICGN mice exhibit proteinuria at a young age, later develop hypoproteinemia, hyperlipidemia, severe anemia and systemic edema, and eventually die as a result of CRD [20,21]. In the kidneys, most of the renal tubules expand and many kinds of extracellular matrix (ECM) components accumulate abnormally in glomeruli and the tubulointerstitium because of the overproduction and stabilization of ECM components, and the inhibition of ECM breakdown [9,29,[31][32][33].…”
mentioning
confidence: 99%